Pertumbuhan, Perkembangan Perakaran, dan Hasil Kecang Hijau pada Tiga Sistem Olah Tanah di Lahan Sawah Irigasi yang Di Pupuk P - Kuswanta Futas Hidayat (Jurnal Agrista, 2008)
Root Growth, Development and Yield of Mungbean in Various Soil Tillage Systems on Irrigated Low Land Fertilized by PABSTRACT. The experiment was carried out to observe root growth and development, and yield of mungbean (Vigna radiata (L.) Wilczek) on irrigated low land as a result of P dosages application and various soil tillage systems. Field experiment was carried out at Kedaloman village, Tanggamus regency of Lampung Province. Field experiment used a split plot pattern in randomized block design. The main plot were soil tillage systems which consisted of tree levels, those were intensive tillage, maximum tillage and no-tillage; and subplot was P dosages which consisted of four levels, those were 0, 9.9, 19.8, and 29.7 kg ha-1 P. The experiment result showed that soil tillage system had no significant effect on length and number of root, volume of root nodule. The highest yield of dry grain was 1.545,1729 g (1,9315 ton ha-1) obtained at optimum dosage 18,0740 kg ha-1 P.